2012
DOI: 10.1103/physreva.85.053841
|View full text |Cite
|
Sign up to set email alerts
|

Two-frequency Jahn-Teller systems in circuit QED

Abstract: We investigate the simulation of Jahn-Teller models with two nondegenerate vibrational modes using a circuit QED architecture. Typical Jahn-Teller systems are anisotropic and require at least a two-frequency description. The proposed simulator consists of two superconducting lumped-element resonators interacting with a common flux qubit in the ultrastrong coupling regime. We translate the circuit QED model of the system to a two-frequency Jahn-Teller Hamiltonian and calculate its energy eigenvalues and the emi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…, N) which impliesᾱ γ,k = 0. Assuming sin(θ j ) = 0, the conditionφ j =φ l =φ solved the second equation in (14). The latter is the arbitrary choice for a direction of spontaneous symmetry breaking where the system chooses a direction along which to order.…”
Section: B Saddle-point Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…, N) which impliesᾱ γ,k = 0. Assuming sin(θ j ) = 0, the conditionφ j =φ l =φ solved the second equation in (14). The latter is the arbitrary choice for a direction of spontaneous symmetry breaking where the system chooses a direction along which to order.…”
Section: B Saddle-point Approximationmentioning
confidence: 99%
“…Here the bosons represent a single or several quantized modes inside of an electromagnetic resonators, while the spin degrees of freedom are implemented either by real two-level atom, or artificial atoms such as quantum dot or superconducting circuit. Recently it was shown that the interaction between the quantum dot [13] or superconducting circuit [14] with two cavity modes leads to the Jahn-Teller coupling. Arranging atoms and resonators in the form of lattice can realize our model (1), with coupling between the resonators provided by the photon hopping.…”
Section: Implementation With Quantum Optical Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacitive coupling between resonators is mediated by C c . A 3-phase Josephson junction flux qubit is used as an artificial superconducting atom simultaneously coupled to each resonator through coupling inductances L c1,c2 of individual inductors [8,19,47]. The coupling strength between resonators is tuned by hopping parameter J = C c ω1ω2 4C1C1…”
Section: A Circuit Layout and Protocolmentioning
confidence: 99%
“…In terms of two superconducting LC resonators coupled with a common two-level artificial atom is used as a simulator in the ultrastrong coupling regime [19]. Two-frequency JT system can be switched to an effective single mode from the two-mode model by tuning the hopping term between the resonator in different coupling regimes [20,21].…”
Section: Introductionmentioning
confidence: 99%